Research hotspots in pediatrics: co-word clustering analysis based on readership in PubMed Central - Deng, Fangming; Sun, Wen; Guo, Jiangwei; Yang, Yujia (Frontiers in Pediatrics, 2024)
Objective: By analyzing high readership articles from the Chinese Journal of Contemporary Pediatrics (CJCP) in the PubMed Central (PMC) database, this study aims to identify research hotspots and trends in the field of pediatrics.Methods: Articles from the CJCP ranked by annual readership in PMC from 2021 to 2023 were collected. Using word frequency analysis and co-word analysis, the thematic characteristics of these articles were explored.The word frequency analysis and co-word analysis revealed four thematic directions that were of significant interest to researchers: (1) current public health or medical events such as COVID-19 and influenza; (2) mental health issues in children and adolescents; (3) pediatric neurological diseases and neurodevelopment; (4) diseases in preterm infants and newborns.This study provides pediatric researchers with a valuable perspective to understand and grasp the development dynamics and future directions in the field of pediatrics.